Characterization of the B-cell receptor repertoires in peanut allergic subjects undergoing oral immunotherapy - Kiyotani, Kazuma; Mai, Tu H; Yamaguchi, Rui; Yew, Poh Yin; Kulis, Mike; Orgel, Kelly; Imoto, Seiya; Miyano, Satoru; Burks, A Wesley; Nakamura, Yusuke (Journal of human genetics, 2018)
B-cell receptors (BCRs) play a critical role in adaptive immunity as they generate highly diverse immunoglobulin repertoires to recognize a wide variety of antigens. To better understand immune responses, it is critically important to establish a quantitative and rapid method to analyze BCR repertoire comprehensively. Here, we developed "Bcrip", a novel approach to characterize BCR repertoire by sequencing millions of BCR cDNA using next-generation sequencer. Using this method and quantitative real-time PCR, we analyzed expression levels and repertoires of BCRs in a total of 17 peanut allergic subjects' peripheral blood samples before and after receiving oral immunotherapy (OIT) or placebo. By our methods, we successfully identified all of variable (V), joining (J), and constant (C) regions, in an average of 79.1% of total reads and 99.6% of these VJC-mapped reads contained the C region corresponding to the isotypes that we aimed to analyze. In the 17 peanut allergic subjects' peripheral blood samples, we observed an oligoclonal enrichment of certain immunoglobulin heavy chain alpha (IGHA) and IGH gamma (IGHG) clones (P = 0.034 and P = 0.027, respectively) in peanut allergic subjects after OIT. This newly developed BCR sequencing and analysis method can be applied to investigate B-cell repertoires in various research areas, including food allergies as well as autoimmune and infectious diseases.